2021
DOI: 10.1177/1471301221994317
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver identity in care partners of persons living with mild cognitive impairment

Abstract: Research on caregiver identity in the context of memory impairment has focused primarily on more advanced stages of the cognitive impairment trajectory (e.g., dementia caregivers), failing to capture the complex dynamics of early caregiver identity development (e.g., MCI; mild cognitive impairment caregivers). The aim of this study was to develop a nuanced understanding of how caregiver identity develops in family and friends of persons living with MCI. Using constructivist grounded theory (ConGT), this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Although some people with MCI function fairly well, a systematic review found that those with MCI felt that they were less relied upon and were a burden to others, and were frustrated with the reactions of family and friends to their reduced cognitive abilities [37]. They might have felt that they were no longer on 'equal terrain' with each other, and there was an experiential shift from the norm of their pre-existing relationship roles, which contributed to tension in the relationship [38]. These earlier studies suggest that the couple relationship had changed into that of a 'patient-caregiver' relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some people with MCI function fairly well, a systematic review found that those with MCI felt that they were less relied upon and were a burden to others, and were frustrated with the reactions of family and friends to their reduced cognitive abilities [37]. They might have felt that they were no longer on 'equal terrain' with each other, and there was an experiential shift from the norm of their pre-existing relationship roles, which contributed to tension in the relationship [38]. These earlier studies suggest that the couple relationship had changed into that of a 'patient-caregiver' relationship.…”
Section: Discussionmentioning
confidence: 99%
“…People with MCI and their partners emphasized cherishing the current moment, possibly because of the nature of MCI. People with MCI and their partners reported that their memory problems were not 'extremely debilitating' , but that they were sometimes confused by changes that they observed, which could be unpredictable and transient [38]. Wadham et al further explained that couples might perceive the future as uncertain but the knowledge of inevitable deterioration provoked distressing emotions, including a sense of hopelessness, powerlessness, and futility [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, carer identity is complex and not a discrete state of being. A study looking at carer identity in patients with early cognitive impairment as opposed to diagnosed dementia, found carers were unsure about the norms associated with being a carer and they did not see themselves as carers as the current needs of their loved one were not severe enough to see themselves in this role [ 16 ]. For this reason, there is an argument that not every carer wants to, or will, identify as a carer and as such we should reconsider encouraging people to develop a traditional carer identity as the only way to facilitate better support for them [ 17 , 18 ].…”
Section: Carer Identificationmentioning
confidence: 99%
“…The concept of caregiver burden is not new and has been evaluated in many studies of PD [ 17 ]. There are also countless studies that have examined the effect of caregiving on identity [ 18 ]. Many studies have focused on the identity change perceived by caregivers of their caree [ 19 ].…”
Section: Introductionmentioning
confidence: 99%